Respuesta :

Answer:

x = 53/6 , y = -55/6

Step-by-step explanation:

Let the 2 numbers be x and y.

x+y = -1/3 ........... (1)

x-y = 18...............(2)

This is a simultaneous equation we will use elimination method.

Add equation 1 and 2

2x = 18 -  ⅓

2x = 17⅔

2x = 53/3

Multiply both sides by 3

6x = 53

Divide both sides by 6

x = 53/6

Put x = 53/6 into equation 1

x+y = -⅓

53/6  + y = - ⅓

y = -⅓ - 53/6

y = -55/6

Therefore x = 53/6 , y = -55/6

I hope this was helpful, please mark as brainliest

Answer:

x = 53/6 , y = -55/6

Step-by-step explanation: